Sustainability in Financial Matters - Baranyi, Aranka; Siklósi, Veronika; Széles, Zsuzsanna (Acta Carolus Robertus, 2022)
The European Environment Information and Observation Network uses the 1987 UN definition of sustainability, which is the maintenance of a process of development that meets the needs of society today, while ensuring that future generations have everything they need to meet their future needs. It is becoming increasingly important what we leave to our grandchildren, that is, to posterity. The concept of social well-being is often mentioned in connection with sustainability, and this has also been reassessed in recent times, if we think of the Covid-19 epidemic, which has led to the protection and preservation of health, among other things, taking precedence over material well-being. The Russian-Ukrainian conflict has made security more important than material well-being for many people. The change in the terminology used in the literature also shows the change in the scope of the issue of well-being, i.e. we are no longer talking about the use of the words 'wealth' or 'welfare', but more and more about the term 'well-being'. In all of this, the achievement of sustainable 'well-being' is inseparable from economic processes and their financial aspects. To achieve sustainable management and operations, not only the right technologies and processes are needed, but also the financial solutions that facilitate their implementation. In recent years, and particularly since the signing of the Paris Climate Agreement, events have accelerated to identify areas for action at all levels and by all actors that can play a role, directly or indirectly, in achieving sustainability as soon as possible. (https://eionet.kormany.hu/a-fenntarthato-fejlodes-fogalma)
Keywords: eco-footprint; green finance; finance; welfare; environmental burden